Evidence on unemployment, market work and household production - Michael C. Burda; Daniel S. Hamermesh (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
Time-diary data from four countries suggest that differences in market time between the unemployed and employed represent additional leisure and personal maintenance rather than increased household production. U.S. data for 2003-2006 show that almost none of the reduction in market work in areas of long-term high unemployment is offset by additional work at home. In contrast, in those areas where unemployment has risen cyclically, reduced market work is largely substituted by additional time in household production.
Keywords: E24; J22; D13; 330; Unemployment; time use; household production; paid work; Langzeitarbeitslosigkeit; Zeitbudgetforschung; Haushaltsproduktion; Erwerbstätigkeit; USA